A. Dolgopolsky's Nostratic Dictionary and Afro-Asiatic (Semito-Hamitic) - Takács, Gábor (Lingua Posnaniensis, 2011)
The Nostratic Dictionary testifies to Dolgopolsky's significant research results contributing to Afro-Asiatic etymology, which is until now hindered by a number of objective circumstances: (1) even we ourselves in the Moscow school only have a general working hypothesis on the basic consonantal correspondences (esp. in the relationship of Proto-Semitic, Egyptian, and Proto-Berber), which have not yet been satisfactorily elaborated and thoroughly tested in all details (esp. in the least explored Omotic and Chadic daughter languages). (2) Secondly, it has always been - almost irrespectively of the individual authors (albeit in different degrees) - difficult in our etymological research, especially in the case of Semitic and Egyptian, to keep a balance between the philological background of our comparanda and their external parallels. Dolgopolsky has worked carefully in order to minimize these unavoidable negative effects. My comments to the following etymological entries that were selected at random mostly carry additional data, new cognates, which signifies the still unexploited immense treasure and possibilities in our domain. May this discussion gain new friends for Nostratic studies and Afro-Asiatic etymology!